Biological basis of emotions. Stress' role in puberty process regulation - Czajkowska-Majewska, Maria Dorota (Studia Ecologiae et Bioethicae, 2008)
Emotions are fundamental functions of mammalian brain, essential for survival of an individual, a group and a species, they have biological basis and are mediated by a variety of neurotransmitters and neurohormones acting on specific brain structures. Stress is state of disturbed homeostasis, which generates a spectrum of adaptive physiological reactions in an organism, which promote individual’s survival or survival of a species. One such adaptive mechanism includes control by stress (via stress hormones) of reproductive functions by either delaying or accelerating puberty.